Management rewired : why feedback doesn't work and other surprising lessons from the latest brain science - Jacobs, Charles S. (New York, N.Y. : Portfolio, 2009)
The founder of the Amherst Consulting Group and managing partner of One Eighty Partners turns current management theory on its head, arguing that organizations that are able to apply brain science to their businesses will overtake the competition and enhance performance at every level. He demonstrates how relying on emotions--rather than logic--leads to better business decisions.
Includes bibliographical references (p. 203-207) and index.
Keywords: Psychology, Industrial; Interpersonal relations -- Psychological aspects; Personnel management -- Psychological aspects; Organizational behavior; Management